Prey items of some amphibians and reptiles in Phu Khieo–Nam Nao Forest Complex, northeastern Thailand - Prapaiporn Thongproh; JIDAPA CHUNSKUL; PEERASIT RONGCHAPHO; CHANTIP CHUAYNKERN; YODCHAIY CHUAYNKERN; RUTTAPON SRISONCHAI; CHIRAWUTH SAENGSRI; PREEYA AONPIME; RATCHATA PHOCHAYAVANICH; PERMSAK KANISHTHAJATA; SAMRET PHUSAENSRI; SUTHIN PROMPALAD; SATAPHON TONGPUN; JIRACHAI ARKAJAG; PRATEEP DUENGKAE (Society for Indonesian Biodiversity, 2020)
Abstract. Thongproh P, Chunskul J, Rongchapho P, Chuaynkern C, Chuaynkern Y, Srisonchai R, Saengsri C, Aonpime P, Phochayavanich R, Kanishthajata P, Phusaensri S, Prompalad S, Tongpun S, Arkajag J, Duengkae P. 2020. Prey items of some amphibians and reptiles in Phu Khieo–Nam Nao Forest Complex, Northeastern Thailand. Biodiversitas 21: 4124-4130. We reported prey items for two amphibians (Fejervarya limnocharis and Sylvirana nigrovittata) and three reptiles (Hebius sp., Bungarus candidus and Xenopeltis unicolor) from several areas of Phu Khieo–Nam Nao Forest Complex (northeastern Thailand) based on direct observation method. Fejervarya limnocharis (Anura: Dicroglossidae) consumed Amynthas sp. (Clitellata: Megascolecidae) in Nam Nao National Park (Phetchabun Province), while Sylvirana nigrovittata (Anura: Ranidae) consumed Megaustenia sp. (Gastropoda: Ariophantidae) in Phu Long Forest (Chaiyaphum Province). Consumption of snails in Sylvirana nigrovittata was documented as the first report on this prey item for the species. In Phu Luang Wildlife Sanctuary (Loei Province), Hebius sp. (Serpentes: Colubridae) consumed Fejervarya limnocharis while Bungarus candidus (Serpentes: Elapidae) consumed Argyrophis muelleri (Serpentes: Typhlopidae). Xenopeltis unicolor (Serpentes: Xenopeltidae) consumed Glyphoglossus molossus (Anura: Microhylidae) in Phu Wiang National Park (Khon Kaen Province).